Vascular Access Site for Renal Replacement Therapy in Acute Kidney Injury: A Post hoc Analysis of the ATN Study - Ng, Yue-Harn; Ganta, Kavitha; Davis, Herbert; Pankratz, V. Shane; Unruh, Mark (Frontiers in Medicine, 2017)
Background: Acute kidney injury requiring renal replacement therapy (RRT) in the ICU portends a poor prognosis. The decisions regarding dialysis catheter placement is based mainly on physician discretion with little evidence to support the choice of dialysis catheter location. Methods: The Veterans Affairs/National Institutes of Health Acute Renal Failure Trial Network Study was a multicenter, prospective, randomized trial of intensive versus less intensive RRT in critically ill patients with AKI. We assessed the association of dialysis catheter location with dialysis catheter related outcomes including catheter related complications, mortality, dialysis dependence and dialysis dose delivered. Results: Of the 1124 patients enrolled in the ATN study, catheter data was available in 1016 (90.39%) patients. A total of 91 (8.96%) subclavian, 387 (38.09%) internal jugular and 538 (52.95%) femoral dialysis catheters were inserted. The femoral group was younger (58.39 ± 16.27), had greater bleeding tendency [lower platelet count (96.00 ± 109.35) with higher INR (2.01 ± 2.19)] and had a higher baseline Sequential Organ Failure Assessment score on admission (14.59 ± 3.61) compared to the other two groups. Dialysis catheter related complications were low in this study with no significant difference in the rates of complications amongst all catheter locations. Mortality and dialysis dependence was lowest in the subclavian group while the dose of dialysis delivered (Kt/V) remained lowest in the femoral group, after propensity score and center adjustments. Conclusion: Patient characteristics influence the choice of dialysis catheter location with a tendency to place femoral catheters in younger, sicker and more coagulopathic patients. There were no statistically significant differences in complication rates among the three catheter locations, although femoral catheters may be associated with a lower delivered dose of dialysis during intermittent hemodialysis.